Perception of the Obafemi Awolowo University Undergraduate Students on F. M. Radio Lecturers - Adeyanju, Lade Joel (2014)
The paper investigated the perception of students' on the use of radio for delivery of lectures on campus. Seventy-four 74 (39 male and 35 female) that registered for the course on Creativity in Education, IED 403 served as subject for the study. Convenient sampling procedure was used for the selection of subject of study. They reacted to a 14 item self-designed questionnaire on perception of students to radio lecture (PSLR). Three research questions on disposition of female and male subjects to radio lecture were tested using percentages, mean scores and standard deviation. T-test was used to test differences between male and female disposition to radio (FM) lecture. Results of the survey reveal that sixty-eight point one, three 68.13 percent of all responses were in favour of radio lecture. Twenty-six point six seven; 26.67 percent were opposed to it, while five point two one 5.21 percent of the responses were undecided about it. Female had a mean score of 24, SD ± 7.4; male subjects had a mean score of 22.7 and SD of ± 9.94. Seventy-eight 78 percent of respondents already had their personal radio sets, while 89.18 percent were listening to instructional programmes from radio. Seventy-eight 78 percent of respondents were prepared to listen to radio broadcast tried out on the university campus in Ile-Ife.